Non-destructive measurement and monitoring of separation of charged particle micro-bunches - Zhang, H; Konoplev, I; Lancaster, A; Harrison, H; Doucas, G; Aryshev, A; Shevelev, M; Terunuma, N; Urakawa, J (AIP Publishing, 2017)
Micro-bunched particle beams are used for a wide range of research including wakefield-based particle acceleration and tunable sources of radiation. In all applications, accurate and non-destructive monitoring of the bunch-to-bunch separation is required. With the development of femtosecond lasers, the generation of micro-bunched beams directly from a photocathode becomes routine; however, non-destructive monitoring of the separation is still a challenge. We present the results of proof-of-principle experiments conducted at the Laser Undulator Compact X-ray accelerator measuring the distance between micro-bunches via the amplitude modulation analysis of a monochromatic radiation signal. Good agreement with theoretical predictions is shown; limitations and further improvements are discussed.